2022
DOI: 10.3389/fsufs.2022.954017
|View full text |Cite
|
Sign up to set email alerts
|

Soil carbon storage potential of acid soils of Colombia's Eastern High Plains

Abstract: Improving soil organic carbon (SOC) storage enhances soil quality and mitigates climate change. Agricultural and livestock specialists increasingly view tropical grasslands as a potential target for storing more soil carbon while boosting productivity. Earlier research in the 1990s showed the promise of improving SOC storage in the Eastern High Plains of Colombia. But these studies were limited to two experimental stations, without focusing on conditions on farms or under variable management. This research exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
(72 reference statements)
0
9
0
Order By: Relevance
“…The CO 2 -eq footprint from pasture establishment and maintenance was assumed on a prorated basis considering 15 years of on-farm productive grazing (Vera and Hoyos, 2019). Fertilizer and tillage imprints were computed from Edwards- Jones et al (2009); Kim et al (2011), and the University of Arkansas (2019) while the estimated range of CO 2eq SOC accumulation rate was based on published reports (Fisher et al, 1994;Rao, 1998;Fisher et al, 1998;Rondoń et al, 2006;Fisher et al, 2007;Costa et al, 2022;Hyman et al, 2022).…”
Section: Functional Scenarios and System Boundariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The CO 2 -eq footprint from pasture establishment and maintenance was assumed on a prorated basis considering 15 years of on-farm productive grazing (Vera and Hoyos, 2019). Fertilizer and tillage imprints were computed from Edwards- Jones et al (2009); Kim et al (2011), and the University of Arkansas (2019) while the estimated range of CO 2eq SOC accumulation rate was based on published reports (Fisher et al, 1994;Rao, 1998;Fisher et al, 1998;Rondoń et al, 2006;Fisher et al, 2007;Costa et al, 2022;Hyman et al, 2022).…”
Section: Functional Scenarios and System Boundariesmentioning
confidence: 99%
“…This is consistent with the view that in the Colombian Orinoquıá, increased SOC storage at deep soil layers (30-100 cm), reduced N 2 O emissions from beef urine deposition, and viable land-based agendas of CO 2 removal from the atmosphere can be achieved through the ability of biological nitrification inhibition, N uptake from the ammonium source, and the deep rooting of B. humidicola (Costa et al, 2022). Hyman et al (2022) showed a large potential for SOC storage in Colombia's Eastern High Plains. They found less SOC storage than Fisher et al (1994) and indicated that earlier high levels of SOC accumulation in well-managed pastures returned to a lower equilibrium value under inadequate management conditions.…”
Section: Estimated Production Patterns Methane Emissions and Carcass ...mentioning
confidence: 99%
“…The aboveground and belowground C stocks and SOC accumulation rates from improved pastures were estimated for the three contrasting SCEs to reflect differences that are not usually captured by animal performance variables and static characteristics. Values on SOC accumulation derived from contemporaneous experiments at CRC and nearby to the current study area were used (Fisher et al, 1994;Rao, 1998;Trujillo et al, 2006;Costa et al, 2022;Hyman et al, 2022). The methods used to determine SOC stocks in different pastures were described by Fisher et al (1994).…”
Section: Estimating Co2-eq Ch4 Footprint C Stocks Rate Of Soc Accumul...mentioning
confidence: 99%
“…Tropical pastures with sown grasses with deep root systems, such as B. humidicola and A. gayanus when well-managed (Fisher et al, 2007) with proper grazing and maintenance fertilizer application (Braz et al, 2013;Saravia et al, 2014) can increase SOC stocks in deep soil layers up to 1 m depth, while soils under poorly managed or degraded pastures may lose SOC over time (Boddey et al, 2010). In this study, our assumed values of SOC accumulation rates of 1 to 3 Mg/ha/year were based on the published reports on above-and below-ground net primary productivity (NPP; Fisher et al, 1998;Kanno et al, 1999;Rao et al, 2001a;Trujillo et al, 2006) and SOC accumulation in long-term pastures in Colombia and Brazil (Fisher et al, 1994(Fisher et al, , 2007Bustamante et al, 2006;Braz et al, 2013;Saravia et al, 2014;Baptistella et al, 2020;Hyman et al, 2022).…”
Section: Estimated C Footprintsmentioning
confidence: 99%
“…Mechanical renovation occurred every 10 years following the frequency recorded in a farm survey of commercial ranches (Vera et al, 1998). Notwithstanding, it is noted that onfarm Bh pastures can persist without reseeding for more than 20 years if reasonably well managed Hyman et al, 2022). Machinery fuel use values and fertilizer inputs were computed and transformed to carbon dioxide equivalent (CO2-eq) emission values.…”
Section: Location and Prototypesmentioning
confidence: 99%